Image plane detection of FRB121102 with the MeerKAT radio telescope. Issue 3 (18th November 2022) - Andrianjafy, J C; Heeralall-Issur, N; Deshpande, A A; Golap, K; Woudt, P; Caleb, M; Barr, E D; Chen, W; Jankowski, F; Kramer, M; Stappers, B W; Wu, J
ABSTRACT: We present the analysis of radio interferometric 2-s images from a MeerKAT observation of the repeating fast radio burst FRB121102 in 2019 September, during which 11 distinct pulses have been previously detected using high time and frequency resolution data cubes. In this work, we detected 6 out of the 11 bursts in the image plane at 1.48 GHz with a minimum peak signal-to-noise ratio (S/N) of 5σ and a fluence detection limit of ∼0.512 Jy ms. These constitute the first detections of a fast radio burst (FRB) or a radio transient using 2-s time-scale images with MeerKAT data. Analysis of the fitted burst properties revealed a weighted average precision of ∼1 arcsec in the localization of the bursts. The accurate knowledge of FRB positions is essential for identifying their host galaxy and understanding their mysterious nature that is still unresolved to this day. We also produced 2-s images at 1.09 GHz but yielded no detection that we attributed to the spectral structure of the pulses that are mostly higher in strength in the upper frequencies. We also explore a new approach to difference image analysis (DIA) to search for transients and find that our technique has the potential to reduce the number of candidates and could be used to automate the detection of FRBs in the image plane for future MeerKAT observations.